Lung & Gynecological Cancers: Has COVID-19 Impacted Patients? - Muhammad Talha Waheed; Mir Ibrahim Sajid; Samira Shabbir Balouch; Adnan Jabbar (BioMedica, 2020)
Coronavirus disease- 2019 (COVID-19) presented as case of viral pneumonia of unknown etiology is diagnosed by Reverse Transcriptase Polymerase Chain Reaction (RT-PCR) test of the samples from upper and lower respiratory tract. It can present as a mild flu-like illness for healthy adults yet it may become a life-threatening disease for the immunocompromised, such as cancer patients, by predisposing them to respiratory pathogens which may manifest as life-endangering pneumonia. Physicians should carefully evaluate their patient’s disease process and tailor treatment for individual patients to ensure that before doing beneficence, no further harm is done. Whether this is a wrinkle in time or the new normal, time will tell, but in light of recent evidence, ‘extra’ caution is the way forward.